Microwave-assisted extraction of lignin from coconut coir using deep eutectic solvents and its valorization to aromatics. (February 2022) - Mankar, Akshay R.; Pandey, Ashish; Pant, K.K.
Graphical abstract: Highlights: Effective delignification of coconut coir using deep eutectic solvent was achieved. ChCl: LA (1:4) gave the highest lignin yield of 82% with >95% purity. Extraction ability of DES was correlated with Kamlet Taft parameters and pKa values. H factor for process was 55.5 due to efficient microwave heating at 150 °C, 20 min. CTH of extracted lignin gave bio-oil yield of 38.8% using Ru/C and isopropanol. Abstract: Lignin is a rich renewable source of aromatics present in lignocellulosic biomass (LCB). The extraction of lignin from the intricate LCB network is a challenging task for successful commercialization of sustainable biorefineries. In the present study, a series of choline chloride (ChCl)-carboxylic acid based deep eutectic solvents (DESs) were used for the extraction of lignin from coconut coir under microwave irradiation. Among the synthesized DESs, ChCl: lactic acid (LA) (1:4) gave the highest lignin yield of 82% with >95% purity. Interestingly, the severity factor (H factor) for the pretreatment process was found to be a significantly lower (55.5) as compared to reported studies due to efficient microwave heating. Moreover, the DES showed good recyclability for four recycle runs thus making it a promising candidate for the delignification of LCB. Finally, the extracted lignin was converted to aromatics via catalytic transfer hydrogenation (CTH) using Ru/C and isopropanol as in-situ hydrogen donor.